Atmospheric effects in space geodesy - Schuh, Harald; Bohm, Johannes (Springer atmospheric sciences, 2013)
Various effects of the atmosphere have to be considered in space geodesy and all of them are described and treated consistently in this textbook. Two chapters are concerned with ionospheric and tropospheric path delays of microwave and optical signals used by space geodetic techniques, such as the Global Navigation Satellite Systems (GNSS), Very Long Baseline Interferometry (VLBI), or Satellite Laser Ranging (SLR). It is explained how these effects are best reduced and modelled to improve the accuracy of space geodetic measurements. Other chapters are on the deformation of the Earth's crust due to atmospheric loading, on atmospheric excitation of Earth rotation, and on atmospheric effects on gravity field measurements from special satellite missions such as CHAMP, GRACE, and GOCE. All chapters have been written by staff members of the Department of Geodesy and Geoinformation at TU Wien who are experts in the particular fields.